GAYA BAHASA PENEGASAN DALAM CERAMAH USTAZ ABDUL SOMAD - Salman Alfarisi; Charlina Charlina; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Language style is a way that is done by someone in conveying information in a beautiful language, both oral and written language to achieve a good impression on the listener or reader. The purpose of this study was to describe the affirmation language style used by ustadz Abdul Somad. Lectures taken in July 2018 were three lectures. Of the three lectures there were 282 affirmation language style data. In this study, the author uses descriptive methods, the steps starting from uploading Ustadz Abdul Somad's lecture video, collecting data, classifying, analyzing, and making conclusions to get an overview of the object under study. The data collection technique carried out in this study was tekik documentation. From the results of data analysis, there are 282 affirmation language style data. 135 repetition language styles, 5 alusio language styles, 7 anticlimactic language styles, 9 climax language styles, 1 antonomasia language style, 39 asidenton language styles, 1 polisidenton language style, 5 elliptical language styles, 1 euphemistic language style, 6 hyperbolic language styles , 4 styles of interrupt language, 2 styles of correction language, 7 styles of pleonas language, 1 style of paraphrase, 12 styles of rhetorical language, 2 styles of synechdoke languages, 33 styles of tautology, 2 styles of exegetical language. Overall the style of repetition is the dominant affirmation style used by Ustadz Abdul Somad.Key Words: Affirmation language style, lecture, ustaz